AN EFFORTS TO INCREASE STUDENTS’ ACTIVENESS USING TEAM GAMES TOURNAMENT IN SMPN 14 SURABAYA - Fitriyah, Farihatil; Syuroyyah, Chalimatus; Brillianti, Sabrina Fatimah; Hidayati, Nur; Faizin, Moh. (UIN Antasari Banjarmasin, 2024)
It is imperative to recognise the significance of student activity in the context of learning, as it serves as an indicator of the efficacy of the teaching and learning process. Furthermore, student activeness is pivotal to the development of their understanding, skills, and meaningful experiences in learning. The present study aims to explore efforts to increase student activeness through the use of the TGT (Team Games Tournament) model in PAI and Budi Pekerti lessons at the junior high school level. The present study employs a descriptive qualitative research method. In March 2024, the researchers conducted the study at SMPN 13 Surabaya in class 8B, with the participation of 30 students. The researchers conducted direct observations of activities in the field related to the issue under investigation. Prior to the implementation of the TGT model in the PAI and Budi Pekerti subjects, the results of the study at SMPN 13 Surabaya in class 8B demonstrated that students exhibited increased levels of activity and enthusiasm following the implementation of the TGT cooperative learning model.